MicroRNAs miR-371-3 in serum as diagnostic tools in the management of testicular germ cell tumours - Dieckmann, K-P (Nature Publishing Group, 2012)
BACKGROUND: miRNAs are small noncoding RNA molecules that can be released into body fluids. Germ cell tumours (GCTs) overexpress miRNAs of the miR-371-3 cluster. Thus, serum levels of these miRNAs may correlate with tumour load. METHODS: miRNAs of the miR-371-3 cluster were quantified in cubital vein blood samples of 20 GCT patients with clinical stage 1, and of 4 patients with advanced stages before and after treatment. In six patients testicular vein blood (TVB) was examined additionally. Seventeen healthy males served as controls. Likewise, expression of miRNAs in 15 matching tumour specimens was measured. RESULTS: In all patients, serum levels of miRNAs 371-3 were much higher than in controls. In stage 1, levels decreased postoperatively 336.7-fold, 7.4-fold, and 7.7-fold for miRNAs 371a-3p, 372, and 373-3p, respectively (P<0.01). Also, in those cases with advanced disease levels dropped to the normal range after completion of treatment. miR-371-3 levels in TVB exceeded those in peripheral blood in all cases. Expression of miR-371a-3p was also documented in tumour tissue. However, no correlation was found regarding the extent of miRNA expression in tissue and the values measured in matching serum. CONCLUSION: Thus, miR-371a-3p serum level appears to be a useful biomarker in GCTs.